?People Like Us?: News Coverage of Food Assistance During the COVID-19 Pandemic (Mary Ann Liebert, 2022)
Objective: To understand how the public discourse around food assistance and social responsibility evolved during the first year of the COVID-19 pandemic by analyzing news coverage. Methods: We conducted an ethnographic content analysis of news articles and photographs about food insecurity or food assistance published by U.S. newspapers and wire services between December 1, 2019, and November 30, 2020. We analyzed a random sample of 241 articles and 223 photographs to assess how they depicted food assistance programs, the program participants, and whether they included cues for deservingness. Results: Before the pandemic, news about food assistance was dominated by stories about abuse and fraud. Once COVID-19 began, news coverage contained cues known to engender beliefs about the deservingness of people receiving assistance. During the pandemic, news also highlighted misconceptions about food assistance programs, called for policy changes to reduce logistical barriers, and described the plight of families and other ?people like us? in need of food assistance. Discussion: News coverage during the pandemic cued audience empathy, highlighted the logistical strains faced by food assistance programs, and elevated values of government accountability. The narrative about society's obligation to care for communities in need can be transferred to other safety net programs that protect the public's health. Health Equity Implications: As the pandemic evolves, public health leaders can maintain the narrative about the importance of food assistance and expand the characteristics of this narrative to challenge well-entrenched, but false, narratives about those who need help.